Mortality and Associated Risk Factors in Community-Dwelling Persons With Early Dementia. (January 2020) - Barrett, Blake; Schultz, Susan K.; Luther, Stephen L.; Friedman, Yvonne; Cowan, Linda; Bulat, Tatjana
Abstract : Objective: Examine mortality and associations with baseline characteristics among Veterans with early dementia. Methods: Participants included dyads of community-based Veterans with early dementia and their caregivers (N=143) enrolled in a previous longitudinal study. Department of Veterans Health Affairs' electronic records were used to retrospectively collect Veteran mortality outcomes, over a 6-year period. Measures included baseline: demographics, dementia-related factors, other comorbid conditions, functioning, and medication use. Associations with baseline characteristics and mortality were examined with bivariate analyses and a series of Cox proportional hazard models. Results: Over 6 years of study follow-up, 53.1% of participants died. The mean time to death was 3.09 years, with a range of 54 days to 5.91 years. Female sex, better cognition, and higher scores on the Tinetti Gait and Balance scale were protective factors in the final multivariable model, adjusting for other characteristics. Conclusions: While newly diagnosed with early dementia, over half of our sample died in the 6-year follow-up period, with the average death occurring only 3 years after initial diagnosis. The finding of lower mortality associated with better performance on gait/balance testing indicates an important opportunity for focused interventions and early detection of gait and balance changes early during cognitive decline.